Analyzing the Influence of the Coal Export Ban Policy on the Financial Performance of PTBA Indonesia: A Case Study of Indonesia’s Coal Company - Riza Syafitri; Dzikri Firmansyah Hakam (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
The demand for coal in Indonesia and globally has risen in response to global population growth. As the largest exporter of thermal coal globally, they exported around 434 Mts in 2021, with primary consumers including India, China, Japan, and South Korea. Indonesian coal mining companies are confronting a coal export prohibition due to insufficient domestic coal supply for PLN amidst the European energy crisis and the Ukraine-Russia crisis. The coal export ban may negatively impact the sales of coal mining companies, such as PTBA, and limit their potential to expand into Italy and Poland in 2022. This study aims to comprehensively analyze PTBA's fair value using internal and external analysis to assess PTBA's financial condition. PTBA shares were valued at US 0.226 or Rp 3,293 using the DCF method in early 2022. A Monte Carlo Simulation will be performed to assess the value at risk and measure potential investment losses. A Monte Carlo Simulation was conducted at a 95% certainty level to determine the valuation range of shares, which was between -US 0.04 and US 0.45. PTBA's current stock is undervalued based on DCF methods, indicating that investors who purchase at US 0.223 or Rp 3,923 may benefit.